2011
DOI: 10.1021/ma200007d
|View full text |Cite
|
Sign up to set email alerts
|

Nanoscale Viscoelastic Behavior of the Surface of Thick Polystyrene Films as a Function of Temperature

Abstract: The variation in the glass transition temperature of thin polymeric films represents a phenomenon yet to be fully explained. To date, it is widely agreed that it is linked to the interfaces that the film forms with the air and the supporting substrate. Herein, we address one of the main issues regarding the viscoelastic behavior of the region near the free interface of thick polystyrene films where a reduction in the glass transition temperature is expected to occur. We have measured, as a function of the temp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
19
0

Year Published

2012
2012
2017
2017

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 26 publications
(20 citation statements)
references
References 45 publications
(97 reference statements)
1
19
0
Order By: Relevance
“…As shown in a previous publication, z increases immediately after the feedback is switched on and flattens out at a value of around 25 nm, depending on the history of the applied voltage to the piezoactuator. This is a typical creep effect and can be evaluated on a rigid sample such as a piece of silicon wafer and its contribution then considered in the data analysis: it has the opposite sign from the tip penetration.…”
Section: Methods Of Analysissupporting
confidence: 61%
See 3 more Smart Citations
“…As shown in a previous publication, z increases immediately after the feedback is switched on and flattens out at a value of around 25 nm, depending on the history of the applied voltage to the piezoactuator. This is a typical creep effect and can be evaluated on a rigid sample such as a piece of silicon wafer and its contribution then considered in the data analysis: it has the opposite sign from the tip penetration.…”
Section: Methods Of Analysissupporting
confidence: 61%
“…In a recent article, we have addressed the issue regarding the decrease in T g at the air interface and the depth of this region . Our approach was based on a direct measurement of the surface indentation as a function of T .…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…1−3 It is suggested that at the free surface of a polymer film a layer of few nanometers of thickness exists, 1,2,4 in which chain motions are faster than in the bulk system. Moreover, depending on the degree of the polymer/substrate interaction, the mobility of polymer chains at the interface with the substrate can be increased, decreased, or remain the same as in the bulk.…”
Section: Introductionmentioning
confidence: 99%